Demand-side management in the Smart City concept - Anatoly P. Dzyuba (Ural State University of Economics, 2020)
In the context of the widespread adoption of information and communication technologies, the key objectives are to enhance the effectiveness of infrastructure management in certain agglomerations and cities, as well as to optimize the use of municipal energy resources. The paper deals with the opportunities and avenues for the use of price-dependent electricity demand management in today’s wholesale and retail electricity markets in Russia within the framework of the Smart City concept. Methodologically, the paper rests on the principles of macroeconomics and the Smart City concept. In the study, the methods of analysis, synthesis, systematization, statistical observation, etc. are applied. The information base of the research includes empirical data on the parameters of uneven electricity consumption by various municipal facilities. The research results show that city electric vehicles, city lighting, pumping stations, electric heating systems, etc. are major electricity consumers, which allow managing the costs incurred in purchasing electric resources at municipal level. The authors develop a model and an algorithm for price-dependent electricity consumption management of municipal facilities in the Smart City concept and test them using the case of the trolleybus network of the city of Chelyabinsk. The study proves the expediency of performing price-dependent electricity consumption management of municipal infrastructure in the Smart City concept.